2019
DOI: 10.21203/rs.2.425/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous noninvasive hemoglobin monitoring estimates timing for detecting anemia better than clinicians: A randomized controlled trial

Abstract: Background Hemoglobin measurement is important for transfusion decision-making. Pulse CO-Oximetry provides real-time continuous hemoglobin (SpHb) monitoring. The triage role of SpHb trends based on hemoglobin measurements was investigated. Methods In this diagnostic randomized controlled trial, 69 patients undergoing spine or cytoreductive surgery were randomly enrolled into SpHb-monitoring and standard-care groups. Diagnostic blood samples were drawn for CO-oximetry Hb (CoOxHb) when the SpHb decreased by 1 g/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
2
1
Order By: Relevance
“…When using the exclusion zones determined by measurement repeatability analysis but not excluding SpHb based on low perfusion index, SpHb concordance was 94.2%. Our findings are also better than reported in 69 patients undergoing spine or cancer surgery that employed a 1 g/dl exclusion zone [ 20 ]. A study of patients undergoing abdominal or pelvic surgery found 41 of 269 changes at any Hb had increased SpHb when ABGHb decreased, including 14 in which the decrease was more than − 1 g/dl [ 11 ].…”
Section: Discussioncontrasting
confidence: 65%
“…When using the exclusion zones determined by measurement repeatability analysis but not excluding SpHb based on low perfusion index, SpHb concordance was 94.2%. Our findings are also better than reported in 69 patients undergoing spine or cancer surgery that employed a 1 g/dl exclusion zone [ 20 ]. A study of patients undergoing abdominal or pelvic surgery found 41 of 269 changes at any Hb had increased SpHb when ABGHb decreased, including 14 in which the decrease was more than − 1 g/dl [ 11 ].…”
Section: Discussioncontrasting
confidence: 65%
“…Tang et al compared the PPV of a SpHb drop with clinical judgement in predicting a haemoglobin drop of > 1.0 g.dl À1 in patients undergoing spine surgery using the Radical-7 â Pulse Co-Oximeter. The PPV was 0.93 in the SpHb group and 0.55 in the non-SpHb group[9]. They also found the PPV to be 0.87 for LabHb < 10.0 g.dl À1 detection with SpHb, whereas our patient sample had a PPV of 0.72 for LabHb < 13.0 g.dl À1 .…”
supporting
confidence: 53%
“…Accuracy studies in different clinical settings for its predecessors reached conflicting conclusions [4][5][6][7][8][9]. A previous study evaluating the ability of non-invasive oximetry haemoglobin (SpHb) in detecting pre-operative anaemia using an older version (Pronto-7 with Rainbow 4D TM sensor (Pronto-7)) found they were unable to obtain stable readings in 20% of patients and had a reduced accuracy in women [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation